Evaluation of the usability of Web-based applications - Đorđević, Nebojša D. (Vojnotehnički glasnik / Military Technical Courier, 2016)
The paper emphasizes the importance of the usability of Web-based applications as an essential condition for attracting and retaining customers. At the beginning of the paper, a general classification of methods for usability evaluation is given in order to show different views of researchers on usability. In order to ensure a Web application lifetime, it is necessary to measure and evaluate many features that affect software usability. The paper gives a brief overview of the most commonly used methods for evaluating the usability of Web-based applications published in the last decade, chosen by the author. Since decision making is not an easy process, the conclusion gives recommendations to be specially considered when selecting a method.